Gender analysis of urban mobility behaviours in the Tunisian Sahel region - El kébir, Mehdi; Ghédira, Aymen (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The integration of gender into questions of everyday mobility has been the focus of scientific research for several years. Despite the breadth of this topic, few studies on gender mobility are conducted in southern countries. This article attempts to fill this knowledge gap and paint a portrait of women’s travel behavior in Tunisia. The study area is the Tunisian Sahel, which was studied as part of a household travel survey conducted in 2019. Based on 2,021 observations, a descriptive analysis of mobility behavior was carried out, providing information about the main travel patterns for both genders in this region. Our analysis deviates from the traditional approach of categorizing women as a unified group, and examining their mobility on an individual basis by considering their income levels. Significant differences were observed between the two genders, which are influenced by the socio-cultural context of Tunisian women and their financial situation. The majority of women are less mobile than men, as more complex journeys are limited to the vicinity of home, and they often rely on public transport. As financial conditions improve for women, travel tends to become easier. Comparing the analytical results of our study with scientific references reveals numerous similarities and differences.